The Local Wisdom of the Andingingi Ritual as a Manifestation of Social Action Among the Kajang Indigenous Community - Syahrul Hidayat; Risky Setiawan; Bustan Bustan (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
The Andingingi ritual is a form of local wisdom among the Kajang indigenous community in Tanah Toa, South Sulawesi, reflecting the harmonious relationship between humans and nature. This study aims to analyze the meaning and motivations behind community participation in this ritual through the lens of Max Weber’s theory of social action, which encompasses traditional action, value-oriented action, goal-oriented action, and affective action. This study employs a qualitative method with an ethnographic approach to understand the meanings, values, and cultural practices within the Andingingi ritual among the Kajang indigenous community. Data collection techniques include indepth interviews, literature review, and documentation. Data analysis was conducted interactively through the stages of data reduction, data presentation, and drawing conclusions using the social action theory framework. The results indicate that the Andingingi ritual functions not only as a tradition passed down through generations but also carries profound symbolic meaning for the Kajang community. Community participation is driven by various motivations, including adherence to tradition, belief in spiritual and moral values, hopes for safety and well-being, and emotional engagement that strengthens social solidarity. Thus, this ritual is a complex social phenomenon that reflects the integration of cultural, rational, value, and emotional aspects in community life. This study underscores the importance of preserving local wisdom as part of cultural identity amidst the tide of modernization.